Trypanocidal Activity of Marine Natural Products - Amy J. Jones; Tanja Grkovic; Melissa L. Sykes; Vicky M. Avery (Marine Drugs, 2013)
Marine natural products are a diverse, unique collection of compounds with immense therapeutic potential. This has resulted in these molecules being evaluated for a number of different disease indications including the neglected protozoan diseases, human African trypanosomiasis and Chagas disease, for which very few drugs are currently available. This article will review the marine natural products for which activity against the kinetoplastid parasites; Trypanosoma brucei brucei, T.b. rhodesiense and T. cruzi has been reported. As it is important to know the selectivity of a compound when evaluating its trypanocidal activity, this article will only cover molecules which have simultaneously been tested for cytotoxicity against a mammalian cell line. Compounds have been grouped according to their chemical structure and representative examples from each class were selected for detailed discussion.